The Influence of Work Environment on Employee Performance at PT. PNM Medan Tembung Area - Fahrul Alam Wardama Pane; Ilham Mubaraq Ritonga; Pitono Pitono (CV Edujavare Publishing, 2024)
This study investigates the influence of the work environment on employee performance at PT. PNM Area Medan Tembung, focusing on both physical and non-physical factors. The purpose of this study was to determine and analyse the influence of the work environment on employee performance at PT. Area PNM Medan Tembung. The sample in this study was 30 employees of PT. Area PNM Medan Tembung. The sampling technique used was purposive sampling, namely determining the sample with certain considerations. The type and source of data were obtained through primary and secondary data. Analysis of the data obtained using simple regression. Based on the results of the research and discussion in this study, it is known that the work environment variable significantly influences the performance of PT employees. PNM Area Medan Tembung which is shown in the significant test, namely t count> t table of 28.225> t-table 2.020 and from the work environment variable on employee performance of 71.7%. When viewed from the descriptive results, the percentage of the work environment variable is included in the high category, namely 139 and the employee performance variable of 139 is also in the high category.